Non-Pharmacological and Pharmacological Stimulation of Glycolytic ATP Production for Treating ROS-Mediated Cellular Senescence - Seledtsov, Victor I.; Delwig, Alexei A. von (Research Perspective on Biological Science Vol. 1, 2025)
Cellular senescence is driven by two interconnected processes: a decline in adenosine triphosphate (ATP) production and an increase in mitochondrial reactive oxygen species (ROS) levels. ATP depletion primarily affects the energy-intensive synthesis of large macromolecules, such as deoxyribonucleic acid (DNA), which are also more susceptible to oxidative damage than smaller biomolecules. Given these dynamics, enhancing ATP generation through anaerobic glycolysis—bypassing mitochondrial ROS production—could help counteract cellular senescence, it was proposed. Clinical studies support this approach. Intermittent hypoxia (IH) therapy has been shown to enhance glycolytic ATP production and reduce oxidative stress in both preclinical models and human trials. IH has demonstrated benefits in sports medicine by improving endurance, muscle regeneration, and recovery. Moreover, studies in elderly populations suggest that controlled IH protocols can enhance cognitive function, increase mobility, and reduce frailty by modulating metabolic pathways and mitigating oxidative damage. In addition, pharmacological strategies targeting mitochondrial function, such as metformin and mild respiratory chain inhibitors, have been shown to upregulate glycolysis while simultaneously reducing ROS production. Clinical trials indicate that metformin extends healthspan by improving metabolic efficiency, reducing inflammation, and attenuating cellular senescence markers. Similarly, preclinical studies suggest that partial inhibition of mitochondrial complex I can stimulate compensatory glycolysis, offering potential therapeutic benefits for cardiovascular, neurodegenerative, and metabolic disorders. A lifelong combination of non-pharmacological (IH therapy) and pharmacological (glycolysis-enhancing and ROS-reducing agents) interventions may significantly slow mitochondrial aging and improve overall healthspan, was proposed. Further clinical trials are warranted to validate these approaches and optimize therapeutic protocols for mitigating ROS-mediated cellular senescence.